Pengaruh Severity, Free Asset Dan Downsizing Terhadap Keberhasilan Turnaround Pada Perusahaan Yang Mengalami Financial Distress (Studi Empiris Pada Perusahaan Sektor Consumer And Goods Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2018) - Novi Darmayanti; Nawari Nawari; Egidia Demmy Andini (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2021)
The research is aimed at knowing the impact of inequality, free assets and downsizing on the turnaround success of companies that are experiencing financial distress conditions in consumer and goods companies in the period 2014-2018. This research is a quantitative explanatory research with purposive sampling technique for data collection.  As many manufacturing companies as samples. This study uses SPSS Application version 25 and logistic regression analysis to test the hypothesis because the independent variable is a combination of metrics and non-metrics. The results showed that free assets and downsizing had no effect on turnaround as evidenced by a significant value greater than 0.05 while severity had a positive effect on turnaround with a significantly smaller result than at 0.05